Editing efficiencies with Cas9 orthologs, Cas12a endonucleases, and temperature in rice - Illa-Berenguer, Eudald; LaFayette, Peter R.; Parrott, Wayne A. (Frontiers in Genome Editing, 2023)
The advent of CRISPR-Cas technology has made it the genome editing tool of choice in all kingdoms of life, including plants, which can have large, highly duplicated genomes. As a result, finding adequate target sequences that meet the specificities of a given Cas nuclease on any gene of interest remains challenging in many cases. To assess target site flexibility, we tested five different Cas9/Cas12a endonucleases (SpCas9, SaCas9, St1Cas9, Mb3Cas12a, and AsCas12a) in embryogenic rice calli from Taipei 309 at 37°C (optimal temperature for most Cas9/Cas12a proteins) and 27°C (optimal temperature for tissue culture) and measured their editing rates under regular tissue culture conditions using Illumina sequencing. StCas9 and AsCas12 were not functional as tested, regardless of the temperature used. SpCas9 was the most efficient endonuclease at either temperature, regardless of whether monoallelic or biallelic edits were considered. Mb3Cas12a at 37°C was the next most efficient endonuclease. Monoallelic edits prevailed for both SaCas9 and Mb3Cas12a at 27°C, but biallelic edits prevailed at 37°C. Overall, the use of other Cas9 orthologs, the use of Cas12a endonucleases, and the optimal temperature can expand the range of targetable sequences.